Medsensio-Sanolla Cardiopulmonary Auscultation Dataset [MSCAD] - a dataset of lung & heart auscultation recordings as well as vitals data for COVID and chronic patients - Mikolaj Pabiszczak; Johan Ravn; Doron Adler; Liran Avraham (Zenodo, 2023)
This is a comprehensive clinical database that contains information from confirmed COVID-19 patients, individuals who are at higher risk for severe COVID-19, and healthy patients. The data was collected as part of the [PyxY.ai project](https://pyxy.ai/), which is funded under the Horizon 2020 program. The dataset has been collected specifically to aid in the development of the PyXy.ai system. The dataset consists of two parts: first part contains 18497 auscultation recordings collected during 1875 encounters with 1333 patients (among the patients: 185 had COPD, 73 had Asthma, 33 had emphysema, 739 had hypertension, 123 had myocardial infarction, 213 had heart failure); the second part consists of 4547 audio recordings collected in 319 encounters with 319 patients (1 encounter per patient). In the first part,60% of recordings corresponds to pulmonary auscultation (in standard locations: left and right: main bronchus, basal segment of lung, apical segment of upper lobe of lung), 40% to cardiac auscultation (aortic valve, pulmonary valve, tricuspid valve, mitral valve). In the second dataset 100% of recordings corresponds to pulmonary auscultation - thispart contains solely pulmonary auscultation recordings. In case of both datasets some vitals data for patients is also provided (i.a., heart rate, blood pressure, pulse oximetry, body temperature). Audio recordings are provided in wav format, vitals data in CSV format as well as HL7 FHIR format. "Medsensio-Sanolla Cardiopulmonary Auscultation Dataset [MSCAD] - a dataset of lung & heart auscultation recordings as well as vitals data for COVID and chronic patients." (c) 2023by Medsensio AS, Sanolla Ltd, Rudolf Riester GmbH, Helgeland hospital trust / Helgelandssykehuset HF, Philonmed GmbH, Benevit holding GmbH, Natali Ltd. "Medsensio-Sanolla Cardiopulmonary Auscultation Dataset [MSCAD] - a dataset of lung & heart auscultation recordings as well as vitals data for COVID and chronic patients." is licensed under a Creative Commons ...